Prognostic value of PET/CT characteristics and combined IPI in follicular lymphoma and diffuse large B-cell lymphoma - LI Zhuohan, HUANG Xinyun, GUO Rui, YI Hongmei, XU Pengpeng, WU Zhifang, LI Biao (Zhenduanxue lilun yu shijian)
Objective The international prognostic index (IPI) has limited ability to distinguish risk levels in patients with follicular lymphoma and diffuse large B-cell lymphoma (FL/DLBCL). This study aims to investigate the diffe-rences in imaging features between FL/DLBCL and DLBCL, and to integrate baseline PET/CT characteristics with clinical parameters to improve the ability of IPI to predict prognosis in FL/DLBCL patients. Methods A total of 65 patients with pathologically confirmed FL/DLBCL treated at our hospital between January 2015 and January 2022 were collected (follow-up duration: 2.4-113.0 months), and a 1∶1 matched group of patients diagnosed with DLBCL during the same period was selected (follow-up duration: 2.9-91.6 months). PET/CT features and survival differences between the two groups were compared. Cox regression analysis was used to identify independent prognostic factors for progression-free survival (PFS) in FL/DLBCL patients, which were incorporated into a nomogram. The predictive value of the model was evalua-ted using the concordance index (C-index) and receiver operating characteristic (ROC) curves. Results Compared with DLBCL, FL/DLBCL patients had a greater maxium distance between two lesions (Dmax) on PET/CT images (55.07 vs. 33.82, P=0.031) and a greater number of total lesions throughout the body (7 vs. 4, P=0.002). The IPI could only distinguish between low-risk and non-low-risk FL/DLBCL groups (P=0.010), but failed to identify patients at high risk of progression (P=0.743). Integrated analysis of PET/CT imaging features and clinical parameters showed that Dmax (HR=3.151, 95%CI: 1.253-7.922, P=0.015) and IPI (HR=3.285, 95%CI: 1.208-8.932, P=0.020) were independent prognostic factors for PFS in FL/DLBCL patients. On this basis, a nomogram was constructed, with a C-index of 0.701. All three global tests (likelihood ratio test, Wald test, and score test) showed high statistical significance (P<0.001). Conclusion FL/DLBCL exhibits more disseminated characteristics on PET/CT images compared to DLBCL. Additionally, Dmax is a highly promising para-meter for prognostic evaluation in FL/DLBCL, and the nomogram constructed based on Dmax and IPI demonstrates excellent discriminatory ability and predictive accuracy in predicting FL/DLBCL survival outcomes.